Acceptability of human papillomavirus (HPV) self-sampling among never- and under-screened Indigenous and other minority women: a randomised three-arm community trial in Aotearoa New Zealand - Naomi Brewer; Karen Bartholomew; Jane Grant; Anna Maxwell; Georgina McPherson; Helen Wihongi; Collette Bromhead; Nina Scott; Sue Crengle; Sunia Foliaki; Chris Cunningham; Jeroen Douwes; et al. (Elsevier, 2021)
Background: Internationally, self-sampling for human papillomavirus (HPV) has been shown to increase participation in cervical-cancer screening. In Aotearoa New Zealand, there are long-standing ethnic inequalities in cervical-cancer screening, incidence, and mortality, particularly for indigenous Māori women, as well as Pacific and Asian women. Methods: We invited never- and markedly under-screened (≥5 years overdue) 30-69-year-old Māori, Pacific, and Asian women to participate in an open-label, three-arm, community-based, randomised controlled trial, with a nested sub-study. We aimed to assess whether two specific invitation methods for self-sampling improved screening participation over usual care among the least medically served populations. Women were individually randomised 3:3:1 to: clinic-based self-sampling (CLINIC - invited to take a self-sample at their usual general practice); home-based self-sampling (HOME - mailed a kit and invited to take a self-sample at home); and usual care (USUAL - invited to attend a clinic for collection of a standard cytology sample). Neither participants nor research staff could be blinded to the intervention. In a subset of general practices, women who did not participate within three months of invitation were opportunistically invited to take a self-sample, either next time they attended a clinic or by mail. Findings: We randomised 3,553 women: 1,574 to CLINIC, 1,467 to HOME, and 512 to USUAL. Participation was highest in HOME (14.6% among Māori, 8.8% among Pacific, and 18.5% among Asian) with CLINIC (7.0%, 5.3% and 6.9%, respectively) and USUAL (2.0%, 1.7% and 4.5%, respectively) being lower. In fully adjusted models, participation was statistically significantly more likely in HOME than USUAL: Māori OR=9.7, (95%CI 3.0-31.5); Pacific OR=6.0 (1.8-19.5); and Asian OR=5.1 (2.4-10.9). There were no adverse outcomes reported. After three months, 2,780 non-responding women were invited to participate in a non-randomised, opportunistic, follow-on substudy. After 6 months,192 (6.9%) additional women had taken a self-sample. Interpretation: Using recruitment methods that mimic usual practice, we provide critical evidence that self-sampling increases screening among the groups of women (never and under-screened) who experience the most barriers in Aotearoa New Zealand, although the absolute level of participation through this population approach was modest. Follow-up for most women was routine but a small proportion required intensive support. Trial registration: ANZCTR Identifier: ACTRN12618000367246 (date registered 12/3/2018) https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=371741&isReview=true; UTN: U1111-1189-0531 Funding: Health Research Council of New Zealand (HRC 16/405) Protocol: http://publichealth.massey.ac.nz/assets/Uploads/Study-protocol-V2.1Self-sampling-for-HPV-screening-a-community-trial.pdf